Simulation of the Air Quality and Evaluation of a Future District Heating System in Valdivia, Chile - Espinoza-Perez, A (Elsevier B.V., 2024)
The city of Valdivia, located in southern Chile, has high levels of particulate matter, mainly due to the heating system based on wood used during winter. As a corrective measure, environmental authorities established the Air Pollution Management Plan for Valdivia in 2017, seeking to decrease the effects on the population s health and provide a better quality of life for inhabitants. An alternative to reduce indoor air quality problems in homes is to implement a district heating plant. This study evaluated the air quality if a district heating plant is implemented in the zone. The WRF-SMOKE-CMAQ model was applied in August 2018 to simulate the effect of this new system on air quality. An adequate fit was achieved for the actual case between the 24-h average concentrations of PM2.5 and PM10 from the simulated and observed values, obtaining correlation factor (r) values of 0.76 and 0.78, respectively. By simulating the scenario with a district heating plant (thus eliminating emissions from residences), it was found that if this plant is located in the southern area of the city, the daily concentrations would be reduced by an average of 53.52% and 51.40% for PM2.5 and PM10, respectively. The results of this study showed that the implementation of a district heating plant results in a reduction in air pollution problems compared to the current scenario, achieving the values established in the primary air quality standards. © 2024 Turkish National Committee for Air Pollution Research and Control